Controlled Reduction of Genomic Heterozygosity in an Industrial Yeast Strain Reveals Wide Cryptic Phenotypic Variation - Sampaio, Nadia M. V.; Watson, Ruth A.; Argueso, Juan Lucas (Frontiers in Genetics, 2019)
Abundant genomic heterozygosity can be found in wild strains of the budding yeast Saccharomyces cerevisiae isolated from industrial and clinical environments. The extent to which heterozygosity influences the phenotypes of these isolates is not fully understood. One such case is the PE-2/JAY270 strain, a natural hybrid widely adopted by sugarcane bioethanol distilleries for its ability to thrive under harsh biotic and abiotic stresses during industrial scale fermentation, however, it is not known whether or how the heterozygous configuration of the JAY270 genome contributes to its many desirable traits. In this study, we took a step toward exploring this question by conducting an initial functional characterization of JAY270’s heteroalleles. We manipulated the abundance and distribution of heterozygous alleles through inbreeding and targeted uniparental disomy (UPD). Unique combinations of homozygous alleles in each inbred strain revealed wide phenotypic variation for at least two important industrial traits: Heat stress tolerance and competitive growth. Quantitative trait loci analyses allowed the identification of broad genomic regions where genetic polymorphisms potentially impacted these traits, and there was no overlap between the loci associated with each. In addition, we adapted an approach to induce bidirectional UPD of three targeted pairs of chromosomes (IV, XIV, and XV), while heterozygosity was maintained elsewhere in the genome. In most cases UPD led to detectable phenotypic alterations, often in opposite directions between the two homozygous haplotypes in each UPD pair. Our results showed that both widespread and regional homozygosity could uncover cryptic phenotypic variation supported by the heteroalleles residing in the JAY270 genome. Interestingly, we characterized multiple examples of inbred and UPD strains that displayed heat tolerance or competitive growth phenotypes that were superior to their heterozygous parent. However, we propose that homozygosity for those regions may be associated with a decrease in overall fitness in the complex and dynamic distillery environment, and that may have contributed to slowing down the erosion of heterozygosity from the JAY270 genome. This study also laid a foundation for approaches that can be expanded to the identification of specific alleles of interest for industrial applications in this and other hybrid yeast strains.